Institutional vs. sectoral dimension of innovation strategies of firms - Stankevičė, Inga; Jucevičius, Giedrius (Technological and Economic Development of Economy, 2014)
In light of the controversy of the dispute about the role of national institutions in shaping innovation strategies of firms, and in light of the lack of explicitness of the notion of innovation strategy within the dispute, this paper aims at ascertaining if national institutional subjection of a firm is fateful in shaping its innovation strategy. The sample companies represented two distinct sets of institutions – Lithuanian vs. Swiss, and two distinct sectors – laser producers vs. contact centres. Warm-house conditions were ensured to eliminate other potentially disruptive factors. Following methods were used to analyse the data: exploratory case study, correlation analysis, test of difference, cluster analysis, and cross-tabulation. The survey highlighted the most important, with regard to national and sectoral disparities, characteristics of innovation strategy.